The Effectiveness of Integrity Pact Signing on Efforts to Eradicate Corruption in the Supreme Court - Farucha, Nathasa (Universitas Sebelas Maret, 2023)
The corruption case that occurred in the Supreme Court was a hard blow to the world of justice in Indonesia. The Supreme Court as the country's highest court and the spearhead of justice in fact still has a gap to be able to commit criminal acts of corruption. Moreover, this case involves the elite ranks of the Supreme Court such as Supreme Court Judges. The Supreme Court is supposed to be an independent, authoritative, accountable judicial institution, and by law has been given independence and self-reliance in fulfilling its judicial aspects. However, it has not been able to create a clean bureaucracy and judicial apparatus. For this reason, as a follow-up to the case, the leadership of the Supreme Court issued an instruction to sign an integrity pact contained in the Circular Letter of the Secretary of the Supreme Court Number 4 of 2022 concerning the Signing of Integrity Pact. This instruction is intended for all judicial apparatus in the Supreme Court and all judicial bodies under it in the context of bureaucratic reform and eradication of corruption. This integrity pact document will later become a commitment of all judicial apparatus to carry out all duties, functions, responsibilities, authorities, and roles in accordance with the provisions of applicable laws and regulations and the ability not to commit corruption. Moreover, this integrity pact has fulfilled the aspects of attachment and legality that have been legally regulated in the legislation. This paper will discuss the integrity pact as a guarantee of a clean and accountable bureaucracy and measure its effectiveness in efforts to prevent and eradicate corruption in the Supreme Court. This paper uses normative-qualitative research methods and literature review methods through literature related to the theme of discussion.